Some New Aspects of Colloidal Systems in Foods - Milani, Jafar M. (IntechOpen, 2019)
Some New Aspects of Colloidal Systems in Foods is a new book on food emulsions, which provides in-depth coverage of some new aspects of food colloids. The coverage includes confident overviews of theoretical issues as well as descriptions of new techniques and recent colloid research findings. Specific topics include the role of electrostatic and steric forces in the stabilization of food colloids, antioxidants in food emulsions, nanoemulsions, and nanostructured colloids in food science. This book can be used as a specialized text for graduate students and researchers in food science and technology. In addition, it will serve as a reference text for advanced students in chemistry, engineers, biochemists, nutritionists, and analytical chemists in the food industry and research.